2002
DOI: 10.1074/jbc.m206738200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Identification of Mouse Vesicular Glutamate Transporter 3 and Its Expression in Subsets of Novel Excitatory Neurons

Abstract: We have cloned and functionally characterized a third isoform of a vesicular glutamate transporter (VGLUT3) expressed on synaptic vesicles that identifies a distinct glutamatergic system in the brain that is partly and selectively promiscuous with cholinergic and serotoninergic transmission. Transport activity was specific for glutamate, was H ؉ -dependent, was stimulated by Cl ؊ ion, and was inhibited by Rose Bengal and trypan blue. Northern analysis revealed higher mRNA levels in early postnatal development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
392
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 369 publications
(435 citation statements)
references
References 83 publications
(96 reference statements)
36
392
2
4
Order By: Relevance
“…As their target cells seem to be confined to the ventral LS and the formation of PB-like terminals was not reported for these afferents they are probably not a candidate for the widespread VGLUT3-innervation of the LS (Groenewegen et al, 1986;Morley, 1986;Risold and Swanson, 1997b). The expression of VGLUT3-mRNA in the substantia nigra pars compacta and ventral tegmental area has been described by Fremeau et al (2002), but was not found by others (Gras et al, 2002;Herzog et al, 2004;Schäfer et al, 2002). The TH-ir projections of the mesencephalon which form pericellular baskets intermingle with the VGLUT3-ir PBs in the LS.…”
Section: Coincidence Of Vglut3-ir With Markers That Define Major Neurmentioning
confidence: 91%
See 3 more Smart Citations
“…As their target cells seem to be confined to the ventral LS and the formation of PB-like terminals was not reported for these afferents they are probably not a candidate for the widespread VGLUT3-innervation of the LS (Groenewegen et al, 1986;Morley, 1986;Risold and Swanson, 1997b). The expression of VGLUT3-mRNA in the substantia nigra pars compacta and ventral tegmental area has been described by Fremeau et al (2002), but was not found by others (Gras et al, 2002;Herzog et al, 2004;Schäfer et al, 2002). The TH-ir projections of the mesencephalon which form pericellular baskets intermingle with the VGLUT3-ir PBs in the LS.…”
Section: Coincidence Of Vglut3-ir With Markers That Define Major Neurmentioning
confidence: 91%
“…Existence of VGLUT3-mRNA was repeatedly reported to be absent from the thalamus, and there are some controversial descriptions for the hypothalamus and ventral pallidum (Fremeau et al, 2002;Herzog et al, 2004;Schäfer et al, 2002). The thalamic afferents are probably represented by VGLUT2-ir as all thalamic subnuclei projecting to the LS express VGLUT2-ir and -mRNA (Fremeau et al, 2001;Herzog et al, 2001;Hur and Zaborszky, 2005;Kaneko et al, 2002;Moga et al, 1995;Staiger and Nürnberger, 1989).…”
Section: Coincidence Of Vglut3-ir With Markers That Define Major Neurmentioning
confidence: 99%
See 2 more Smart Citations
“…Three isoforms of VGLUT have so far been established. Two are recognized as definitive markers of glutamatergic neurons and their axon terminals (VGLUT1, VGLUT2) (Bellocchio et al, 1998(Bellocchio et al, , 2000Takamori et al, 2000;Fremeau et al, 2001Fremeau et al, , 2002Herzog et al, 2001;Hisano et al, 2002;Hisano, 2003) and a third is expressed by cholinergic and serotonergic neurons (VGLUT3) (Gras et al, 2002;Schafer et al, 2002). VGLUT1 mRNA expression in distinct regions of rat and human brain has been confirmed by in situ hybridization studies (Ni et al, 1994(Ni et al, , 1996Hisano et al, 2002;Hioki et al, 2003;Hisano, 2003).…”
mentioning
confidence: 95%